PEMERIKSAAN ALAT BUKTI DALAM PENETAPAN TERSANGKA BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 21/PUU-IV/2014 DIPERSIDANGAN PRAPERADILAN DIKAITKAN DENGAN TUJUAN PRAPERADILAN - Desliza Amalia Wibowo; Davit Rahmadan; Syaifullah Yophi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Pretrial in Indonesia has been regulated through Law Number 8 of 1981 concerningthe Code of Criminal Procedure. Pretrial institutions are intended to test the lawfulness orlawfulness of an arrest and/or detention, the lawfulness of stopping investigations or stoppingprosecutions, and requests for compensation or rehabilitation, so that law enforcementofficials are not arbitrary in carrying out their duties. Over time the authority of lawenforcement then increased with the birth of Constitutional Court Decision Number 21 / PUU-IV / 2014, the decision stated that the authority of pretrial institutions included also in termsof testing the validity or not of the determination of a suspect someone. So that pretrial courtjudges must then focus the examination process on evidence, which is then used as a guidelineto assess whether the actions of law enforcement officials in the investigation and prosecutionstage are legitimate or not someone is determined to be a suspect. However, in fact there is noconsistency in the decisions of pretrial judges where in some cases evidence is tested forrelevance and in some cases the judge does not test it or can be mentioned as long as there aretwo pieces of evidence alone are enough to establish a person as a suspect Therefore it needsto be studied stimulantly first, b How is the implementation of cases in pretrial trials in theexamination of evidence in the determination of suspects based on the decision of theConstitutional Court Number 21 / PUU-IV / 2014, second, the ideal formulation of theexamination of evidence in the determination of suspects at pretrial hearings in Indonesia.This research is a normative legal research or known as legal research, namely byexamining literature materials (secondary data) that have a relationship with the problemsstudied assisted by primary, secondary and tertiary data. This study used qualitative dataanalysis that elaborated descriptively from the data obtained.From the results of the study, it was concluded that, First, the implementation of theConstitutional Court decision Number 21 / PUU-IV / 2014 is the absence of procedures fromjudges in deciding pretrial cases where in some cases the judges check the validity or relevanceof evidence and some do not check, Second, It is necessary to reform the criminal law byformulating an ideal concept for the face of Indonesian pretrial related to the obligation ofjudges to examine the relevance of evidence and the obligation to examine potential suspects.Keywords: Pretrial – Evidence – Suspect Determination